(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article considers the significance of using post-reading activities in secondary schools in foreign language teaching. Most often times, what all the teachers focus on is the pre-reading activities and they simply forget the value of having post-reading activities. By writing this article, I want to show why it is important to have a set of activities after a while-reading in teaching and how it can benefit to the learners effectively and efficiently. Additionally, this article focuses on the common post-reading activities and analyze a few of them